Effect of Psychoeducation on Reducing Burden Among Primary Caregivers of People with Schizophrenia (Jagannath University Journal of Life and Earth Sciences, 2024)
Schizophrenia is a serious psychological illness that needs long-term treatment. Family members, especially those who care for a patient at home, experience the burden of providing long-term care. Psychoeducational intervention may enhance the caregiver’s outcomes. The major goal of the study was to explore the effect of psychoeducation on reducing the burden among primary carers of people with schizophrenia. In this study, thirty-two participants (32 caregivers) were purposefully selected based on the National Institute of Mental Health (NIMH).  A personal information form and the Bangla version of the Zarit Burden Interview scale were administered. Total participants were divided by simple randomization into two groups (i.e., experimental and control groups). Following the baseline evaluation by questionnaire, the experimental group of 16 caregivers received two sessions of psychoeducation, but the control group of the same number of caregivers did not. The effectiveness of psychoeducation was evaluated using a pretest-posttest control group design. Findings suggested that psychoeducation decreased the level of burden, and after the intervention, the mean score of the experimental group was lower than that of the control group. These findings found that the psychoeducation intervention had a positive outcome in reducing the burden on caregivers of patients who deal with schizophrenia.Jagannath University Journal of Life and Earth Sciences, 9(1): 81–94, 2023 (June)